1st International Symposium on Philosophy of Library and Information Science Ethics September 3-5 2014 Kastamonu, Turkey: Evaluation and Recommendations - Hasan S. Keseroğlu; Güler Demir; Elsa Bitri; Ayşenur Güneş (Türk Kütüphaneciliği)
This article includes abstracts, critiques of a part and general analyses of proceedings presented at the 1st International Symposium on Philosophy of Library and Information Science Ethics organized on September 3-5, 2014 in Kastamonu University with the main theme of “Ethics: Theory and Practice”.